Anatomy of a murder: telemetric footprints. - Mond HG; Valentine BC; Randall RD; Kelsall R; Gregory M (Pacing & Clinical Electrophysiology, 2002)
A man with complete heart block received a Pacesetter Affinity pacemaker, programmed DDD. Two months later, the patient was beaten to death and the coroner requested telemetric information. Pacemaker stored Event Records for the previous 40 hours were retrieved and using the zoom scale, the events leading to death were examined. This included sinus tracking during the beating followed by atrial and ventricular pacing interpreted as an unconscious vagal response associated with profound blood loss. Then followed a chaotic rapid ventricular activity or terminal ventricular fibrillation. The telemetric footprints provided valuable time stamps on the events preceding the victim's death.